Annual Dynamics Of Physical Training Of Schoolchildren - H.Z.Bakhriddinov; Makhkamov Sh; Sultonov U (Zien Journals, 2022)
Thе article examines the annual dynamics of physical characteristics of students aged 14-15 in high school, such as speed, strength, speed, strength and endurance.
Keywords: physical culture; physical education; physical qualities; speed